The occurrence of back pain in physiotherapists - Ożóg, Piotr; Natański, Dawid; Zukow, Walery (Journal of Education, Health and Sport, 2019)
Introduction: Back pain is one of the most common problems of the movement system. The physiotherapist’s physiotherapist’s long-term commitment to static body positioning and high-intensity motion, often also the height-weight divergence between the therapist and the patient, leads to the painful role of the patient. The aim of the study: Determining whether physiotherapists suffer from back pain, what the nature of those ailments are, and how their seniority affects them. Determining whether the area of ​​discomfort associated with regular sports or severe spinal injuries and the impact of sports on the intensity of pain. Material: There were 35 participants (21 women and 14 men) - physiotherapist, aged 25-63 (mean 38 years). Methodology: The survey questionnaire (questions on age, sex, height, weight, length of service, occupational specificity, spine pain, VAS scale and modified Laitinen questionnaire) were used in the study group. Results: Statistical analysis revealed the incidence of pain in the spine and their dependence on length of service, the area of the most frequently reported pain and their nature. The impact of physical activity and previous injuries to the spine on the episode in which the pain was present was not shown. Conclusions: Occupational physiotherapist is associated with chronic spinal-backbone ligament dominance, which may be related to the standing position of the work most commonly found in the study group. There was no relationship between the regular exercise of sport and the intensity of the pain experienced, as well as the dependence of the painful spine and sport or previous spinal injuries.